Nativism and Modernity : Cultural Contestations in China and Taiwan under Global Capitalism - Lai, Ming-yan (SUNY series, Explorations in Postcolonial Studies, 2009)
Nativism and Modernity is the first comparative study of xiangtu nativism in Taiwan and xungen nativism in China. It offers a new critical perspective on these two important literary and cultural movements in contemporary Chinese contexts and shows how nativism can be a vital form of place-based oppositional practice under global capitalism. While nativism has often been viewed in nostalgic terms, Ming-yan Lai instead focuses on the structural implications of nativist oppositional claims and their transformations of marginality into alternative discursive spaces and practices. Through contextual analysis and close readings of key texts, Lai addresses interdisciplinary issues of modernity and critically explores the two nativist discourses' various engagements with power relations covering a multitude of social differentiations, including nation, class, gender, and ethnicity.